Accounting information in innovative small cap firms: evidence from London's Alternative Investment Market. Issue 4 (7th June 2021) - Filip, Andrei; Ghio, Alessandro; Paugam, Luc
Abstract : We posit that investors and social media users place more weight on cash flows than on earnings for innovative small cap firms and that, in turn, innovative small cap firms (i) manage cash flows more than earnings, and (ii) disclose more cash flow than earnings information on social media. Using a matched sample of innovative and non-innovative small cap firms listed on the London's Alternative Investment Market (AIM), we document that the value relevance of cash flows (earnings) is higher (lower) for innovative compared to non-innovative small cap firms. Using Twitter to examine the demand of accounting performance measures, we find that Twitter users more frequently retweet and include as 'Favorite' information about cash flows, than information about earnings for innovative small cap firms. We then show that innovative small cap firms engage less intensively in earnings management and exhibit higher abnormal cash flows compared to non-innovative small cap firms. Innovative small cap firms emphasise more information in their tweets about cash flows and less about earnings compared to non-innovative small cap firms. Cross-sectional tests demonstrate that seasoned equity offerings provide additional incentives to engage in increasing abnormal cash flow management activities.